Foreword - –, (Baltistica, 2017)
The present fascicle of Baltistica is devoted to Wojciech Smoczyński, a recognized scholar in Indo-European and Baltic historical linguistics, emeritus Professor of Jagiellonian University in Cracow and Doctor honoris causa of Vilnius University. I would like to thank Dr. Dariusz R. Piwowarczyk for the original idea and the search for contributors. The usual procedures of selection and blind peer review were applied to all articles.Editor
Keywords: –